Assessment of Behavior Abnormalities of Corticosteroids in Children with Nephrotic Syndrome. (16th April 2013) - Youssef, Doaa Mohammed; Abdelsalam, Mohamed Mohamed; Abozeid, Ali Mohamed; Youssef, Usama Mahmoud
Abstract : Introduction . The objective of this work was to define the frequency and severity of steroid related behavioral side effects in children with steroid sensitive idiopathic nephrotic syndrome (SSNS) during Treatment for relapse. Methods . 30 pediatric patients with steroid sensitive nephrotic syndrome were studied; known as SSNS at complete remission or low dose of Prednisolone and have relapse on follow up. All children in this study were subjected to full history taking, thorough clinical examination, assessment socioeconomic standard, and assessment of pediatric quality of life, a battery of psychometric tests included pediatric anxiety, depression, and aggression scores. Results . Our results revealed that there are highly significant increase in the mean values of anxiety, depression and aggression among cases starts to appear on week one and extends to three, five and seven weeks compared to baseline. In the seventh week of follow up cases show significant positive correlation between prednisone doses and mean values of anxiety and depression scores and aggression. Conclusion . we concluded that all studied children with SSNS often experience significant problems with anxiety, depression, and increased aggression during high dose steroid therapy.